2020
DOI: 10.1134/s1064229320080074
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Dye on a Tunisian Unsaturated Layered Soil: Physical and Numerical Modeling

Abstract: The main objectives of this study is to model the transport of methylene blue (MB) in homogenous and layered soils which has been studied experimentally by fixed bed column. The effect of soil stratification has been studied through numerical investigation based on the coupled solute transport model in three-layered soil. The effect of some significant parameters such as flow rate, initial concentration of MB, thickness of each layer and the numbers of layers on the breakthrough curves have been undertaken. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Land application of textile organic waste and crop irrigation waters polluted by dyehouse effluents provide the driving force for the movement of synthetic dyestuffs through agricultural soil. At a low flow rate, the dye–soil contact time is high and a bonding interaction between the dye molecules and soil particles is possible, resulting in an intensification of dye retention on soil materials (Jedidi et al, 2020 ; Smaranda et al, 2017 ); adsorption on soil subsurface is one of the most important processes that allow the dye transport (Jedidi et al, 2020 ). The dye tracer Brilliant Blue FCF (C.I.…”
Section: Resultsmentioning
confidence: 99%
“…Land application of textile organic waste and crop irrigation waters polluted by dyehouse effluents provide the driving force for the movement of synthetic dyestuffs through agricultural soil. At a low flow rate, the dye–soil contact time is high and a bonding interaction between the dye molecules and soil particles is possible, resulting in an intensification of dye retention on soil materials (Jedidi et al, 2020 ; Smaranda et al, 2017 ); adsorption on soil subsurface is one of the most important processes that allow the dye transport (Jedidi et al, 2020 ). The dye tracer Brilliant Blue FCF (C.I.…”
Section: Resultsmentioning
confidence: 99%
“…The transport process of pollutants in layered soil is more complex and can be influenced by soil texture [22], layer arrangement [23,24], soil thickness [25], and the number of layers [26]. Wang et al [27] found that the infiltration peak changes significantly when passing through soil stratification interfaces, and that both clay-sand and sand-clay interbed structures can impede the infiltration process of water.…”
Section: Introductionmentioning
confidence: 99%
“…As a good adsorbent, clay minerals are widely used to remove heavy metals, antibiotics, dyes, etc. from the aqueous environment [ 17 , 18 , 19 ]. The adsorption properties of soil benefit from the large surface area, which improves adsorption by promoting ion exchange [ 20 ].…”
Section: Introductionmentioning
confidence: 99%